Warming Temperatures, Yield Risk and Crop Insurance Participation. (31st July 2021) - Wang, Ruixue; Rejesus, Roderick M; Aglasan, Serkan
Abstract: Previous literature have shown that warming temperatures due to climate change are likely to decrease mean crop yields and increase crop yield risk. However, there is limited understanding of how crop insurance participation can potentially affect the adverse crop yield impacts of warming (or extreme heat). This study specifically examines whether crop insurance participation influences the impact of extreme heat on yield risk (i.e. yield variance, skewness and kurtosis). We utilise a parametric moment-based method and county-level panel data to evaluate how crop insurance participation affects the relationship between warming temperatures and the moments of crop yield distributions. Our results indicate that the yield risk increasing effect of warming is further magnified under high levels of crop insurance participation. This result still holds even when allowing for long-run adaptation (although the crop insurance effect tends to be weaker in this case). In general, our results indicate that not only does crop insurance participation adversely impact mean yields under climate change, it also influences the extent by which warming affects yield variability over time. This supports the notion that crop insurance can serve as a disincentive for climate change adaptation in agriculture.